Diseño de un mecanismo de movilidad, presencia y canales múltiples como tendencias innovadoras de atención al cliente de la empresa Akros Cía. Ltda., localizada en Quito con aplicación a las pymes de servicios tecnológicos - Aguirre Reza, María Rebeca (2015)
The job have four chapters, in each one explains the steps for a design of a mechanism of mobility, presence and multiple channels as innovative trends of attention to the client of the company AKROS CIA. LTDA. Located in Quito, which be apply to the PYMES of technological services. To begin the study, I search the theoretical part that includes concepts and stages that allow understanding and helping the project. An introduction details to the Customer Relationship Management - CRM - in order to know the scene where be the tools designed. For understand the actual situation of the company AKROS CIA. LTDA there is an analysis of the internal factors that influence directly with the development of the company, focused in knowing the capacities that the company possesses. In this chapter are used diverse tools of investigation and management that allow the compilation of information, as well as to specify and qualify the same ones and present an offer of a mechanism of mobility, presence and multiple channels. In the following chapter the financial evaluation of the project is elaborated to demonstrate their importance. Finally, Conclusions and recommendations are established, chords to the accomplishment of each one of the stages for the implementation of the tools of satisfaction to the client.